The wicked redhead : a wicked city novel - Williams, Beatriz (Williams, Beatriz. Wicked city novel., 2019)
1924. Ginger Kelly wakes up in tranquil Cocoa Beach, Florida, having fled south to safety in the company of disgraced Prohibition agent Oliver Anson Marshall and her newly-orphaned young sister, Patsy. But paradise is short-lived. Marshall is reinstated to the agency with suspicious haste and put to work patrolling for rumrunners on the high seas, from which he promptly disappears. Gin hurries north to rescue him, only to be trapped in an agonizing moral quandary by Marshall<U+2019>s desperate mother. 1998. Ella Dommerich has finally settled into her new life in Greenwich Village, inside the same apartment where a certain redheaded flapper lived long ago...and continues to make her presence known. Having quit her ethically problematic job at an accounting firm, cut ties with her unfaithful ex-husband, and begun an epic love affair with Hector, her musician neighbor, Ella<U+2019>s eager to piece together the history of the mysterious Gin Kelly, whose only physical trace is a series of rare vintage photograph cards for which she modeled before she disappeared. Two women, two generations, two urgent quests. But as Ginger and Ella track down their separate quarries with increasing desperation, the mysteries consuming them take on unsettling echoes of each other, and both women will require all their strength and ingenuity to outwit a conspiracy spanning decades.